Temperature and pressure dependence of the some elastic and lattice dynamical properties of copper - Kazanc, S.; Ciftci, Y. O.; Colakoglu, K.; Ozgen, S. (Elsevier, 2006)
In this work, molecular dynamics (MD) simulations are performed for copper using the modified form of the Morse potential function in the framework of Embedded Atom Method (EAM). The temperature- and pressure-dependent behaviours of the bulk modulus, linear-thermal expansion coefficients (a), second-order elastic constants (SOEC), and phonon frequencies are calculated and compared with the experimental data and the other theoretical works. The obtained results are in good agreement with the available experimental findings. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: molecular dynamics simulation; embedded atom method; elastic constants; phonons